“Skepticism and Idealism in G.E Moore’s ‘Proof of an External World’” - Burdman, Federico (2015)
G.E. Moore’s argument in “Proof of an External World” seems to beg the question against the skeptic and to miss the point of the challenge posed by skeptical hypotheses. I propose an interpretation that frees the argument from both charges. Starting from a distinction between the way Moore understood his dialectical position against the idealist and the skeptic, I attempt to illuminate the conception of skepticism that lies behind his argument. I propose that the argument’s core is found in a strong anti-Cartesian statement, even though its relevance for epistemology is to be found in its potential as a stance regarding justification which is closer to the problematic of Pyrrhonic skepticism.